Navicordulia aemulatrix sp. nov. (Odonata, Corduliidae) from northeastern Santa Catarina State, Brazil - Pinto,Ângelo Parise (2010)
Navicordulia aemulatrix sp. nov. (holotype male deposited in MZSP: Brazil, Santa Catarina State, [São Bento do Sul municipality, 26°14'58"S, 49°22'59"W], [railroad station] Rio Vermelho, II.1952) is described and illustrated based on three males. The long cercus (2.9-3.2 mm) places this species in the longistyla-group together with N. kiautai, N. longistyla and N. nitens but it differs from them mainly by the shape of cercus, with carinated part occupying 0.33 of cercus total length, and also by dorsal, ventro-medial and ventro-lateral tubercles developed. An unusual process on tergal portion of prothorax is reported for the first time in Navicordulia. The rate of description of new species of South American 'Corduliidae' is discussed. A map with records of Atlantic Forest Navicordulia species and a list of Brazilian corduliids by state are also presented.